2004
DOI: 10.1080/13657300409380355
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of mud crab farming under different production systems in India

Abstract: Apart from penaeid shrimp culture, crab farming and fattening and other several diversified aquaculture practices are now emerging as viable ventures in India. About 11 types of crab products are being exported from India with an average unit value realization of US$ 3.73 kg -1 , pinpointing its importance in the foreign exchange earnings. An economic evaluation of mud crab culture, fattening and fattening with composite culture of shrimp/finfish has been attempted in this paper. The major operating cost was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 3 publications
(4 reference statements)
1
14
0
1
Order By: Relevance
“…Socio-economic studies in Bangladesh and India under different farming systems (e.g. Ferdoushi and Guo, 2010; Jahan and Islam, 2016; Sen and Homechaudhuri, 2017) have shown that small-scale aquaculture systems have proven to be a lucrative activity which also have the potential to contribute to the wider economic context (Sathiadhas and Najmudeen, 2004).…”
Section: Natural Physical and Financial Capital And The Transformingmentioning
confidence: 99%
“…Socio-economic studies in Bangladesh and India under different farming systems (e.g. Ferdoushi and Guo, 2010; Jahan and Islam, 2016; Sen and Homechaudhuri, 2017) have shown that small-scale aquaculture systems have proven to be a lucrative activity which also have the potential to contribute to the wider economic context (Sathiadhas and Najmudeen, 2004).…”
Section: Natural Physical and Financial Capital And The Transformingmentioning
confidence: 99%
“…Global aquaculture production (including aquatic plants) with 110.2 million tonnes and first‐sale value estimated at USD 243.5 billion in 2016 is one of the fastest growing food production sectors representing 44.2% of world fish production (FAO, 2018). Amidst the overwhelming production of shrimp among the brackishwater species, mud crab Scylla serrata is widely regarded as one of the most promising alternatives to penaeid shrimp culture (Khan & Weelden, 2017; Sathiadhas & Najmudeen, 2004). It is a high valued and fast growing species, and its culture is progressing rapidly because of its promising profitability.…”
Section: Introductionmentioning
confidence: 99%
“…Standard financial performance of aquaculture fisheries production was used (Adams et al, 2001;Brown et al, 2002;Goode et al, 2002;Fong et al, 2005;Liu & Sumaila, 2007;Sathiadhas & Najmudeen, 2004). Data was collected for both inshore and offshore production, income and cost were calculated annually, and then the net present value (NPV) was calculated for a ten year production period.…”
Section: Methods Of Analysesmentioning
confidence: 99%